2020
DOI: 10.1080/02713683.2020.1744164
|View full text |Cite
|
Sign up to set email alerts
|

Normative Database of Peripapillary Vessel Density Measured by Optical Coherence Tomography Angiography and Correlation Study

Abstract: Purpose: To provide a normative data set of swept-source optical coherence tomography angiography (SS-OCTA) peripapillary vessel density (VD) measurements and assess correlations with age, gender, disc area and axial length (AL). Material and Methods: This was an observational cross-sectional study conducted on 346 right eyes of healthy subjects. Peripapillary SS-OCTA VD measurements were obtained in the retinal superficial capillary plexus (SCP), deep capillary plexus (DCP), and choriocapillaris (CC) in all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(101 reference statements)
2
10
0
Order By: Relevance
“…Further analysis showed that vertical peripapillary VD was significantly higher compared with the horizontal measurements [15]. In our study, a similar finding was observed that VD in the superior quadrant and inferior quadrant was significantly higher than the temporal and nasal quadrants.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further analysis showed that vertical peripapillary VD was significantly higher compared with the horizontal measurements [15]. In our study, a similar finding was observed that VD in the superior quadrant and inferior quadrant was significantly higher than the temporal and nasal quadrants.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Mansoori et al found no association between sex and papillary VD in 52 healthy subjects using RTVue XR 100 Avanti OCT [26]. Another study also showed no association between sex and VD of the papillary area [15]. Consistent with those results, age and sex were not significantly associated with the optic disc's superficial VD in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mean difference of vessel density in SRCP and RPC segments between the ON fellow eyes and healthy controls was 1.18% (95% CI, −2.30, −0.06) and 1.71% (95% CI, −3.00, −0.42). As the OCT‐A technique is relatively new, few large normative OCT‐A databases have been reported (Bazvand et al 2017; Rao et al 2017; Fernandez‐Vigo et al 2020). Among those studies, Fernandez‐Vigo et al (2020) reported a mean vessel density of superficial RPC segments of 57.2 ± 5.7 (SD) % in 346 healthy subjects using the Triton device (Topcon) that we also used.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as OCTA is relatively new, normative data are developing [87][88][89], with some unknowns regarding the correlation between general parameters and vessel density [90]. There is systematic variation in FAZ area between devices (measuring higher with Heidelberg than Canon devices) but with a very high intraclass correlation coefficient (ICC) of 0.96 [91], compared to an ICC for flow index of 0.62-0.67 [92] and vessel density of 0.74-0.81 [93].…”
Section: Oct Angiographymentioning
confidence: 99%